2005
DOI: 10.1364/ol.30.001273
|View full text |Cite
|
Sign up to set email alerts
|

Evanescent field-based optical fiber sensing device for measuring the refractive index of liquids in microfluidic channels

Abstract: We report a simple optical sensing device capable of measuring the refractive index of liquids propagating in microfluidic channels. The sensor is based on a single-mode optical fiber that is tapered to submicrometer dimensions and immersed in a transparent curable soft polymer. A channel for liquid analyte is created in the immediate vicinity of the taper waist. Light propagating through the tapered section of the fiber extends into the channel, making the optical loss in the system sensitive to the refractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(143 citation statements)
references
References 13 publications
3
139
0
1
Order By: Relevance
“…Benefitting from the large fractional evanescent fields of a waveguiding MNF, the intensity-dependent MNF sensor usually offers high sensitivity in either air or liquid solutions. In 2005, Polynkin et al reported a MNF optical sensor for measuring the refractive index of liquids in microfluidic channels [23]. By measuring the refractive-index-dependent leakage loss of 1.5-μm-wavelength light guided in a 700-nm-diameter silica MNF, they realized an accuracy of refractive-index measurement of 5.3 × 10 -4 .…”
Section: Mnf Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benefitting from the large fractional evanescent fields of a waveguiding MNF, the intensity-dependent MNF sensor usually offers high sensitivity in either air or liquid solutions. In 2005, Polynkin et al reported a MNF optical sensor for measuring the refractive index of liquids in microfluidic channels [23]. By measuring the refractive-index-dependent leakage loss of 1.5-μm-wavelength light guided in a 700-nm-diameter silica MNF, they realized an accuracy of refractive-index measurement of 5.3 × 10 -4 .…”
Section: Mnf Sensorsmentioning
confidence: 99%
“…(2) Strong evanescent field Strong evanescent field offers strong near-field interaction between the MNF and its surroundings, making the MNF highly favorable for optical sensing [21][22][23][24][25][26][27][28][29][30][31][32] and evanescent coupling between the MNF and other waveguides (e.g., a semiconductor [33,34], metal [35,36] nanowire or planar waveguide [37]) or a substrate [30,35,38,39]. Based on the high-efficiency evanescent coupling, a variety of optical components or devices (e.g., loop and knots resonators [40][41][42][43][44][45][46][47][48][49][50][51], lasers [52][53][54][55][56][57][58], and sensors [21][22][23][24][25][26][27]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By embedding an OM in a transparent low refractive index polymer (Sylgard 184, also called PDMS) in proximity of a fluidic channel [9], the evanescent field of the mode propagating in the OM overlaps with the microfluidic channel, thus the refractive-index difference between the polymer and the fluid strongly affects the OM transmission. The accuracy in the loss measurement affects the minimum measurable refractive index change, which resulted to be of the order of ~5·10 -4 .…”
Section: Microfluidicmentioning
confidence: 99%
“…Polymers have been used as sensing media because they can absorb gas and their optical properties change when impregnated by gases. Bare silica OMFs were used to detect sub-monolayers of chemicals absorbed on their surface [48]. Molecules and their agglomeration dynamics were recorded on a second to minute scale.…”
Section: A Linear Devicesmentioning
confidence: 99%